2017
DOI: 10.1021/acs.jpcc.7b07511
|View full text |Cite
|
Sign up to set email alerts
|

Band Alignment at Au/MoS2 Contacts: Thickness Dependence of Exfoliated Flakes

Abstract: We investigated the surface potential (V surf ) of exfoliated MoS 2 flakes on bare and Au-coated SiO 2 /Si substrates using Kelvin probe force microscopy. The V surf of MoS 2 single layers was larger on the Au-coated substrates than on the bare substrates; our theoretical calculations indicate that this may be caused by the formation of a larger electric dipole at the MoS 2 / Au interface leading to a modified band alignment. V surf decreased as the thickness of the flakes increased until reaching the bulk val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 41 publications
3
72
0
Order By: Relevance
“…The SiO 2 thickness was controlled by varying the oxidation time and measured by cross‐sectional scanning electron microscopy. The MoS 2 monolayers were initially grown on 300 nm thick SiO 2 /Si substrates and then transferred to the SiO 2 /Si substrates with the various SiO 2 thicknesses using poly(methylmethacrylate) layers as described in the previous publication …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SiO 2 thickness was controlled by varying the oxidation time and measured by cross‐sectional scanning electron microscopy. The MoS 2 monolayers were initially grown on 300 nm thick SiO 2 /Si substrates and then transferred to the SiO 2 /Si substrates with the various SiO 2 thicknesses using poly(methylmethacrylate) layers as described in the previous publication …”
Section: Methodsmentioning
confidence: 99%
“…Direct contacts of metal and TMDC layers can alter the majority carrier type and carrier concentration in TMDC layers . Theoretical calculations and experimental results have shown that the overlap of the wave functions of TMDC and metal layers forms electric dipoles at their interface, which modify the electrical properties of the TMDC layer . Insertion of a subwavelength‐thick dielectric layer between TMDC and metal back‐reflecting layers could weaken the interaction between electrons in the TMDC and metal layers .…”
mentioning
confidence: 99%
“…Kelvin probe force microscopy (KPFM), a scanning-probe-based technique, has been widely used to measure local surface potential ( V S ) 1121 . The V S measurements of TMD materials are very useful to identify the number of layers 1113 , study the photo-carrier generation processes 13,14 and estimate the built-in potential at the heterojunctions 15,16 . Since surface adsorbed molecules, such as H 2 O and O 2 , can transfer charges to the TMD materials, the measurement environment and the sample preparation procedures can significantly vary the measured V S of TMD materiaels 1114,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…The light exposure can cause not only the photo-carrier generation/separation but also charge transfer from/to adsorbed/desorbed molecules. All these processes should be considered to explain the light-induced V S change 13,14,19,20 . Careful measurements and analyses of the V S of TMD-metal nanostructures will enable us to achieve better understanding of their physical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Depletion region formation at MoS 2 homojunctions, heterojunctions, and metal junctions has been modeled and investigated by many groups [17,18,19,20]. Nipane et al [21] modeled the electrostatics of lateral junctions in atomically thin materials using line charges representation, Sohn et al [22] investigated the electrostatic band alignment at Au/MoS 2 contacts as a function of the thickness of MoS 2 exfoliated flakes, and Chiu et al [23] determined the band alignment in single-layer MoS 2 /WSe 2 heterojunctions using micro X-ray photoelectron spectroscopy and scanning tunneling microscopy (STM).…”
Section: Introductionmentioning
confidence: 99%